Safety And Efficacy Of The Application Of The Tumor-Treating Fields (Ttfields) Mechanism Associated With Temozolomide After The Standardized Protocol Of Chemotherapy And Radiotherapy In Patients With Recently Diagnosed Glioblastoma - da Silva Gomes, Samuel; Felipe Gusmão Santiago, César; Gonçalves Pereira Guimarães, Débora; Maia Costa Lima, Lucianne; Vinicius Calfat Maldaun, Marcos (Revista Unimontes Científica, 2020)
Abstract: Tumor-Treating Fields is an antineoplastic treatment modality that consists in the application of alternating electric currents directly to the skin in the tumor region. Glioblastoma multiforme is the most common primary brain tumor. Treatment options are limited. A bibliographical review addressing what is significant and new in the medical literature regarding the treatment of glioblastoma with the Tumor-Treating Fields or Novocure mechanism is presented, based on the main research portals. The main objective of this study was to establish the safety and efficacy of the Tumor-Treating Fields approach in the treatment of recently diagnosed glioblastoma. After confirming its safety and efficiency the secondary objective was to establish this approach as the treatment of choice for this pathology. The main articles in English concerning this issue were searched on the portals PUBMED, Cochrane, Lilacs, and Embase. The investigated approach should be added to the first line treatment of glioblastoma in association with microneurosurgery, radiotherapy, and temozolomide.